Application of Artificial Intelligence (AI) and Machine Learning (ML) in The Halal Food Industry: A Bibliometric Review - Novianti, Dewi; Maika, M. Ruslianor (Jurnal Iqtisaduna, 2025)
This study aims to determine the development and productivity of a publication related to “Application of AI and ML in the Halal Food Industry”. Data was collected from the Scopus database using keywords such as “AI In Halal Food Industry”, “Machine Learning In Halal Food Industry”, and “Technology In Halal Food Industry”. This research uses quantitative methods with bibliometric analysis. Based on the search results, researchers obtained 101 documents which were then exported in CSV format and processed using the R (Bilioshiny) Program software and VOSviewer. The analysis included four main metrics, namely most relevant sources, most relevant authors, document types, and keyword occurrence networks. The findings of this study reveal collaboration patterns, publication trends, and the contribution of artificial intelligence (AI) and machine learning (ML) technologies in supporting the development of the halal food industry. These results show that the application of AI and ML in the halal food industry continues to grow, providing opportunities for further research that is more in-depth and applicable in the future.